2014
DOI: 10.1185/03007995.2014.907140
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative effectiveness and safety of rivaroxaban and warfarin in nonvalvular atrial fibrillation patients

Abstract: This analysis suggests that rivaroxaban and warfarin do not differ significantly in real-world rates of composite stroke and systemic embolism and major, intracranial, or GI bleeding. Rivaroxaban, however, was associated with significantly fewer VTE events and significantly better treatment persistence compared with warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
79
3
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 16 publications
17
79
3
17
Order By: Relevance
“…Comparison of separate data for rivaroxaban with warfarin could not be extracted from 2 papers; adjusted HRs between OAC comparisons were lacking in 16; no separate AF data could be extracted from 1 paper with mixed disease states. Finally, 17 observational studies [7][8][9][10][11][12][20][21][22][23][24][25][26][27][28][29][30][31] were included in our analysis, with 3 comparing rivaroxaban versus dabigatran, 9-11 11 comparing rivaroxaban versus Warfarin, 20-27,29-31 and 3 evaluating both comparisons. 7,8,12 Studies with new users and switchers are shown in Table I in the online-only Data Supplement.…”
mentioning
confidence: 99%
“…Comparison of separate data for rivaroxaban with warfarin could not be extracted from 2 papers; adjusted HRs between OAC comparisons were lacking in 16; no separate AF data could be extracted from 1 paper with mixed disease states. Finally, 17 observational studies [7][8][9][10][11][12][20][21][22][23][24][25][26][27][28][29][30][31] were included in our analysis, with 3 comparing rivaroxaban versus dabigatran, 9-11 11 comparing rivaroxaban versus Warfarin, 20-27,29-31 and 3 evaluating both comparisons. 7,8,12 Studies with new users and switchers are shown in Table I in the online-only Data Supplement.…”
mentioning
confidence: 99%
“…The baseline period was defined as the 12‐month continuous health plan enrollment period prior to the index date and the observation period was defined as the period from the index date until whichever event of the following occurred first: end of 12 months of follow‐up, end of continuous health plan enrollment, end of data availability, end of continuous treatment (applied for the continued cohort only), or re‐initiation of oral anticoagulants (applied for the discontinued cohort only). Variables measured during the baseline period include demographics, year of index date, type of index VTE (DVT, PE, or both), VTE identified in the hospital or outpatient/ER, time from first VTE to first rivaroxaban dispensing, Quan‐Charlson comorbidity index (CCI), RIETE bleeding score,20 baseline healthcare resource utilization and costs, risk factors for VTE (including risk factors from the ACCP Evidence‐Based Clinical Practice Guidelines list)21 and bleeding 15…”
Section: Methodsmentioning
confidence: 99%
“…Rivaroxaban, an oral direct factor Xa inhibitor anticoagulant indicated for acute and extended treatment of VTE,13 has been demonstrated as a viable alternative therapy to traditional vitamin K antagonist (VKA) therapy with advantages of minimal drug and food interactions and no requirement for routine coagulation monitoring 13, 14, 15. Findings from a pair of phase III clinical trials have shown that extended treatment with rivaroxaban for an additional 6–12 months is safe and effective to decrease VTE recurrence risk in patients with VTE who have previously completed 6 or 12 months of anticoagulant therapy 14, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Данные реальной клинической практики подтвер-ждают эффективность и хороший профиль безопасности ривароксабана, который демонстрирует значительно бо-лее высокие показатели приверженности к лечению в сравнении с варфарином [43]. В Дрезденском регистре применения НОАК у больных с ФП большие крово-течения при приеме ривароксабана 1 р/д развивались с частотой 3,1% в год [44], а 81,5% пациентов про-должали лечение этим антикоагулянтом при среднем периоде наблюдения 544 дня [45].…”
Section: использование ривароксабана у больных с фибрилляцией предсерunclassified
“…Поскольку долгосрочные исходы терапии пациентов с ФП, веро-ятно, будут зависеть от различий в приверженности к различным режимам приема пероральных антикоа-гулянтов, важно оценить предпочтение и возможное влияние препаратов на исходы при их приеме 1 или 2 р/д. Сообщалось о том, что больные с ФП, принимав-шие ривароксабан, отличались значительно более вы-соким уровнем приверженности (частоты регулярно-го соблюдения назначенного режима повторного прие-ма препаратов) в течение 3-х и 6-месячных периодов наблюдения по сравнению с показателями при лечении варфарином -84,5 против 75,6% и 81,5 против 68,3%, соответственно (р<0,0001 для обоих сравне-ний) [43]. По данным ретроспективного когортного ана-лиза антикоагулянтной терапии в США, включавшего более 32000 пациентов с ФП, получавших ривароксабан или варфарин, первый из препаратов больные чаще принимали без длительных перерывов и реже отка-зывались от лечения по сравнению с приемом варфа-рина [50].…”
Section: оNce-daily Anticoagulant In Atrial Fibrillationunclassified